Estudo da injeção de água e alteração da razão volumétrica de compressão para mitigação da detonação e melhoria do desempenho de um motor de combustão interna - Deborah Domingos da Rocha (2018)
The numerical simulation of an internal combustion engine is an important tool for the development of new technologies constantly integrating the automotive sector to improve engine performance. In this work, water injection and volumetric compression ratio modification were implemented numerically to mitigate knock and promote a better engine performance. Initially, experimental conditions for an engine operating at 6bar, using E27, with a compression ratio of 15:1, and at a speed of 2000rpm, with knock occurrence detected, were reproduced numerically through 3D-CFD analysis using STAR-CD. This simulation was validated with experimental data and then water injection and compression ratio modification techniques were applied to investigate their potentials in reducing knock tendency and improving engine performance. Water injection was performed for 10%, 15%, 20%, and 25% water-fuel ratio mass fractions and it was made using direct injection and port water injection strategies to study the most favorable water injection condition. Then, a spark timing modification analysis was carried out to the final simulations in order to compare their performance at the same condition, which is the knock borderline. All water injection percentages resulted in a reduction of knock tendency and the direct injection strategy for 20% of water allowed a higher spark advance. Despite the lower spark advance increase provided by the 10% water direct injection, it eliminates knock occurrence and provides the best engine performance, since it leads to an indicated power increase correspondent to 3.89% and raised the IMEP approximately 0.84%, besides a fuel consumption reduction of 3.50%. Furthermore, all simulations with water injection and spark timing modification presented lower values for the maximum in-cylinder temperature, even for the simulation that showed the highest pressure, in which 20% of water was injected. The compression ratio modification to 14:1 allowed increasing IMEP and indicated power approximately 0.53% when compared to the original compression ratio at knock borderline